Seismic Shot Point Navigation Data from J Anomaly Ridge and Southeast Newfoundland Ridge acquired during the R/V Knorr expedition KN179-01 (2004) (IEDA: Marine-Geo Digital Library, 2013)
This data set was acquired with the LDEO Portable HiRes Multi-Channel Seismic system during R/V Knorr expedition KN179-01 conducted in 2004 (Chief Scientist: Dr. Richard Norris). These data files are of ASCII format and include Seismic Shot Point Navigation data that provide the primary seismic navigation source for this cruise. Data were acquired as part of the project: The Atlantic Deep Western Boundary Current During the Early Eocene Warm Period, and funding was provided by NSF grant: OCE02-21012.